Policy Rifts in UK Further and Higher Education - Shattock, Michael (International Higher Education, 2021)
The future of further education is under challenge in the United Kingdom. The government appears to see further education solely in terms of supporting the economy through the provision of an improved skills base. An alternative approach would be to bring coherence into the governance and management of further and higher education to create a tertiary education system. Implicit in adopting such an approach would be some decentralization of policy to regions, away from central government.